GOVERNMENT INTERNAL CONTROL SYSTEM IMPLEMENTATION IN Dr. M. YUNUS GENERAL HOSPITAL BENGKULU - Padli Padli; Fahrudin JS Fareke; Sugeng Susetyo (UNIB Press, 2021)
The purpose of this research is to knew government internal control system implementation in Dr. M. Yunus general hospital Bengkulu. This research is a descriptive research. The population of this study is 42 people. The sample of this study was taken by census method. Data analysis in this research use descriptive statistic method. The results showed that the environment control dimension in government internal control system is accordance with government regulation number 60 year 2008, risk assessment and control activities dimensions are not fully accordance with government regulation number 60 year 2008, communication and information dimensions in accordance with government regulation number 60 Year 2008, and the internal control monitoring dimensions is accordance with government regulation number 60 year 2008. Suggestion for Dr. M. Yunus general hospital Bengkulu is to improve the realization of the role of effective internal government oversight apparatus, improve the risk assessment not maximal, especially on risk assessment in the workplace in accordance with government regulation number 60 year 2008. Improving and able to establish and review on performance indicators and measures in accordance with government regulation number 60 Year 2008, maintaining and improving communication and information that has been in accordance with government regulation number 60 year 2008 by utilizing various existing communication means and improving monitoring that has not been maximally monitored by conducting continuous monitoring in accordance with government regulation number 60 year 2008.